FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR PAJAK (Studi pada Wajib Pajak Orang Pribadi yang Memiliki Usaha Warung Kopi di Kota Banda Aceh) - Rahmawaty Rahmawaty; Endang Surasetyo Ningsih; Wida Fadhlia (Program Magister Akuntansi Unsyiah, 2011)
This research aimed to examine and analyze factors that affect willingness to pay taxes. These factors are the awareness of tax paying, knowledge and understanding of taxation regulation, and good perception of the effectiveness of the tax system.Data of this research was collected through questionnaires distribution to the taxpayer who has coffee shop business in Banda Aceh. The data were analyzed using the SPSS program to test whether the model used in this study appropriates as the model analyzed.The empirical results show that not all the above factors has influence on the willingness of taxpayers to pay taxes, only the awareness of tax paying has influence on the willingness of taxpayers. The other factors that are knowledge and understanding taxation regulation and good perception of the effectiveness of the tax system have not significant impact on the willingness to pay taxes. This research is expected to give a view to related parties that are constantly faced to the extensification and intensification of taxes about how to solve this problem. The solution requires hard work from the Tax Service Office to make socializing even harder to the taxpayers, thus increasing the knowledge and understanding of taxation regulation, also good perception of the effectiveness of the tax system. Therefore, it can help increase the willingness of taxpayers to pay taxes. Keywords: willingness to pay taxes, pay taxes awareness, knowledge and understanding of taxation regulations, a good perception of the taxation system.